Do segundo corpo: reflexões sobre os investimentos na imaterialidade - SANTOS, Flávia Martins dos (2010)
In the act of making the body more competitive in the market for appearances and more consistent with the subjectivity of individuals, two trends are evident: the expenditure of time, money and pain in an attempt to enhance the body by processes such as fitness, cosmetics and surgical interventions, and the desire to overcome the physical reality by means of scanning processes of the body, exemplified by the various moving avatars in virtual worlds third dimension such as Second Life. This study aims to identify the projection of contemporary subjectivities in the construction of virtual bodies, spurred by a supposedly imaginary post-human as well as reflect on the nature of the avatar, to identify investments for the construction and improvement of virtual bodies, and analyze the experiences bodily and everyday communication in cyberspace. For this purpose it is necessary for theoretical covering the body, subjectivity and cyberspace, composed by authors such as Foucault (1977, 2000, 2003, 2007), Le Breton (2007), Sibilia (2003, 2004), Deleuze (1988, 1991 ), Rüdiger (2002, 2007), Levy (1996, 1999, 2003), Baudrillard (1991, 1995, 2003), Guattari (1996, 2006), Maffesoli (1996, 1998, 2005), Lipovetsky (2004, 2005, 2007 ), among others. Through virtual ethnographic research technique, proposed by Hine (2004) and Kozinets (1997), was created avatar researcher Lia Olifone, which spent six months in interaction with other avatars within Second Life. In conclusion of this ethnographic experience, we establish the thesis that the avatar in that environment appears to be far beyond a mere representation body, but a locus of free trial, a marker of presence and status, which appears to be closely linked to individual that controls for subjective process. In its construction process, the avatar still has a strong influence of consumer society. It was observed that despite the numerous opportunities offered by reconfiguring the metaverse, there is a tendency to reproduce the social structures and patterns present in the body "first life". However, this reproduction features a one body sociality and aseptic, seeking to root out the negative traits considered, especially with regard to the embodiment, showing some influence of the imaginary post-human.